2014
DOI: 10.1177/1557988314564593
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comorbidities on Prostate Cancer Stage at Diagnosis in Florida

Abstract: To examine the association of major types of comorbidity with late-stage prostate cancer, a random sample of 11,083 men diagnosed with prostate cancer during 2002-2007 was taken from the Florida Cancer Data System. Individual-level covariates included demographics, primary insurance payer, and comorbidity following the Elixhauser Index. Socioeconomic variables were extracted from Census 2000 data and merged to the individual level data. Provider-to-case ratio at county level was alsocomputed. Multilevel logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…The evidence on the effects of chronic diseases on cancer stage is mixed, with some studies indicating an association with advanced stage [19][20][21][22][23][24][25][26][27][28][29][30][31] , others showing no effect [32][33][34] and some reporting a reduced risk of advanced stage 19,22,25,28,31,34,35 for patients with chronic diseases (Figure 1). Hereafter we report estimates only if statistically significant.…”
Section: Cancer Stage At Diagnosismentioning
confidence: 99%
“…The evidence on the effects of chronic diseases on cancer stage is mixed, with some studies indicating an association with advanced stage [19][20][21][22][23][24][25][26][27][28][29][30][31] , others showing no effect [32][33][34] and some reporting a reduced risk of advanced stage 19,22,25,28,31,34,35 for patients with chronic diseases (Figure 1). Hereafter we report estimates only if statistically significant.…”
Section: Cancer Stage At Diagnosismentioning
confidence: 99%
“…Symptom cluster was categorized into none, any one of these three symptoms, any two of these three symptoms and all of these three symptoms b χ 2 test cluster may be because these symptoms can indicate more advanced disease at diagnosis [31,32]; thus, physical symptoms here may simply be acting as a marker of more advanced cancer. Similarly, presence of comorbid conditions has been linked with higher stage at prostate cancer diagnosis [33].…”
Section: Factors Associated With the Symptom Clustermentioning
confidence: 99%
“…For example, men with prostate cancer and preexisting congestive heart failure were more likely to be diagnosed with advanced prostate cancer compared to those without congestive heart failure. 3,30 Although the current study found that elderly men with chronic conditions other than cardiometabolic, respiratory, or mental health conditions were 43% more likely to be diagnosed with advanced prostate cancer, future research studies should examine the impact of less common conditions such as inflammatoryrelated conditions, smoking associated disorders, and sexually transmitted disease on prostate cancer risk, as these conditions also share common risk factors for developing prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…2 A greater number of preexisting chronic conditions or higher chronic condition score can affect prostate cancer stage at diagnosis. [3][4][5][6][7][8] However, the association between preexisting chronic conditions and cancer stage at diagnosis may differ by types of chronic conditions because of the differential pathophysiological pathways of underlying diseases and prostate cancer. For example, the presence of cardiovascular disease may increase the risk of prostate cancer as it shares common risk factors for the development of aggressive prostate cancer, such as the presence of high cholesterol level and obesity.…”
Section: Introductionmentioning
confidence: 99%